A Cross-Sectional, Population-Based, Seroepidemiological Study of Rift Valley Fever in Cameroonian Cattle Populations - Bronsvoort, Barend Mark; Kelly, Robert Francis; Freeman, Emily; Callaby, Rebecca; Bagninbom, Jean Marc; Ndip, Lucy; Handel, Ian Graham; Tanya, Vincent Ngwang; Morgan, Kenton Lloyd; Ngwa, Victor Ngu; Rossi, Gianluigi; Nfon, Charles K.; et al. (Frontiers in Veterinary Science, 2022)
Rift Valley fever (RVF) is an important emerging zoonoses causing abortion and neonatal deaths in livestock and haemorrhagic fever in humans. It is typically characterised by acute epidemics with abortion storms often preceding human disease and these events have been associated with the El Niño weather cycles. Outside of areas that experience epidemics little is known about its epidemiology. Here we present results from a serological study using biobanked samples from a study of cattle conducted in 2013 in 2 sites in Cameroon. 1458 cattle from 100 herds were bled and sera screened using a commercially available RVF ELISA. The overall design adjusted animal-level apparent seroprevalence of RVF exposure for the Northwest Region (NWR) of Cameroon was 6.5% (95% CI: 3.9-11.0) and for the Vina Division (VIN) of the Adamawa Region was 8.2% (95% CI: 6.2-11.0). The age stratified serological results were also used to estimate the force of infection and the age-independent estimates were 0.029 for the VIN and 0.024 for the NWR. The effective reproductive number was ~1.08. Increasing age and contact with wild antelope species were associated with an increased risk of seropositivity while high altitudes and contact with buffalo were associated with reduced risk of seropositivity. The serological patterns are more consistent with an endemically stability rather than the more typical epidemic patterns seen in East Africa. However, there is little surveillance in livestock for abortions storms or in humans with fevers in Cameroon and it is therefore difficult to interpret these observations. There is an urgent need for an integrated One Health approach to understand the levels of human and livestock related clinical and asymptomatic disease and whether there is a need to implement interventions such as vaccination.